Value of Al-amanah in human’ Life - Samsudin, Sofiah; Islam, Md. Sirajul (IJSRP INC, 2015)
Al-Amanah (honesty) is the first requirement to be a real success in the world and rewarded in the Day of Judgment. Nevertheless, many people are inattentive to fulfil it in their daily life. Consequently, corruption, violence and anti-social activities are an everyday occurrence throughout the world. Therefore, the main objective of this study is to focus on the value of al-Amanah in humans’ daily life. The study concentrates on the Qur’anic ayat which talk about al-Amanah in various aspects of humans’ life, its implementation to obtain the satisfaction of Almighty Allah through performing all His commands and avoiding all that He prohibits. The study found whoever careless in fulfilling al-Amanah, he is doing violence to his self as well as leading to acts of corruption, violence and anti-social activities in societies throughout the world. However, the person who performs Allah’s orders and avoids His prohibitions it means he fulfils al-Amanah for his wellbeing and leading to others in performing it.